Evaluation of Coretax Implementation from the Fiscus and User Perspectives: A Case Study of Primary Tax Service Office X and Tax Consultant Office Y - Annisaa Dina Azzahra; Hanung Triatmoko; Trisninik Ratih Wulandari; Saktiana Rizki Endiramurti; Asaprima Putra Karunia (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2025)
This study aims to analyze the challenges and corresponding solutions encountered during the implementation of the Core Tax Administration System or CTAS (abbreviated as Coretax), the latest innovation from the Directorate General of Taxes (DGT), from the perspectives of tax officials (fiscus) and tax consultants. This study employs a case study method with a descriptive approach. Data were obtained through observations and interviews with relevant parties at KPP Pratama X and KKP Y. This research serves as a medium for elucidating the efforts of tax authorities in addressing obstacles during CTAS implementation, as well as a platform for expressing user perspectives, particularly those of tax consultants. The results show KPP faced several challenges, including network issues, system readiness, procedural changes requiring adaptation, and reliance on centralized infrastructure. Mitigation measures included continuous monitoring, the establishment of a direct communication forum with central authorities, service adjustments, socialization initiatives, and the introduction of policies waiving administrative penalties. Both KPP and KKP stakeholders concur that, despite ongoing challenges, the system is developing and holds substantial potential to achieve its objective of modernizing tax administration to enhance user accessibility, provided consistent improvements are sustained.